Soil Fertility Management-A Mirror to Sustainable Agriculture - Qureshi, A.; Singh, D. K.; Kumar, Amrendra (International Journal of Economic Plants, 2017)
Soil fertility is the capacity to receive, store and transmit energy to support plant growth. These processes require healthy soils-living, self-organizing systems with physical, chemical and biological components all functioning and in balance. Continuous use of acidic or salty synthetic fertilizers, insecticides, fungicides and herbicides disrupts this delicate balance. Organic farming has recognized this, but needs to follow its leaders to active soil fertility management. Carbon, in particular, is of critical importance and needs to be maximised through capture with solar energy through photosynthesis by green plants, and optimum storage and use in the soil. Before we can hope to improve systems, however, we need to understand (1) why they are the way they are, and then (2) how science and practice can help to actively manage soil biology to improve and maintain soil fertility, and achieve more sustainable, healthy and productive farming systems -even on our fragile Australian soils in a highly variable and changing climate.